Three‐dimensional analysis of extrahepatic cholangiocarcinoma and tumor budding. Issue 4 (3rd July 2020) - Yoshizawa, Tadashi; Hong, Seung‐Mo; Jung, DongJun; Noë, Michaël; Kiemen, Ashley; Wu, Pei‐Hsun; Wirtz, Denis; Hruban, Ralph H; Wood, Laura D; Oshima, Kiyoko
Abstract: Advances in tissue clearing and microscopy make it possible to study human diseases in three dimensions (3D). High‐grade tumor budding is known to be associated with poor prognosis in various cancers; however, little is known about the 3D architecture of tumor budding. Using tissue clearing, we analyzed the 3D structure of tumor budding and E‐cadherin expression in 31 extrahepatic cholangiocarcinomas. A total of 31 thick slabs (up to 5 mm) were harvested from surgically resected tumor tissue, including 27 hilar and 4 distal cholangiocarcinomas. Twenty‐eight cases were adenocarcinoma, and three were undifferentiated carcinoma. After clearing, the tissues were immunolabeled with antibodies to cytokeratin 19 and to E‐cadherin, and then visualized using light‐sheet and confocal laser scanning microscopy. Tumor budding was evaluated in hematoxylin and eosin–stained sections (2D) using standard pathological criteria. Of the 31 cancers, 13 showed low‐grade tumor budding and 18 showed high‐grade tumor budding. First, 3D analysis revealed that the neoplastic cells in tumor buds of adenocarcinoma were typically not individual islands of cells, but rather tips of attenuated protrusions connected to the main tumor. Second, adenocarcinomas with low‐grade tumor budding were composed predominantly of tubules that only focally form cords at the periphery. By contrast, adenocarcinomas with high‐grade tumor budding predominantly formed cords in both centers and peripheries of the tumors. Third, adenocarcinoma with low‐grade tumor budding was characterized by a few short protrusions with few branches, whereas adenocarcinoma with high‐grade tumor budding was characterized by longer protrusions with more branching. Finally, immunolabeling of E‐cadherin was stronger in the center of the adenocarcinoma but decreased at the tips of protrusions. E‐cadherin loss was more extensive in the protrusions of high‐grade tumor budding than in the protrusions of low‐grade tumor budding. Our findings suggest that tumor buds as seen in 2D are, in fact, cross‐sections of attenuated but contiguous protrusions extending from the main tumor. © 2020 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.